Method for preparing nanoscale noble metal catalyst through cyanide-free electroplating and application of nanoscale noble metal catalyst in electrocatalytic reduction of carbon dioxide
By preparing nano-scale precious metal catalyst composite electrodes in organic composite electrolyte and electrolyzing under specific voltages, the problems of low efficiency and unstable coating of nano-scale precious metal catalysts are solved, and efficient carbon dioxide electroreduction is achieved, and the Faraday efficiency of carbon monoxide is exceeded 82%.
Patent Information
- Application Number
- CN202411766554.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-04
- Publication Date
- 2025-03-04
AI Technical Summary
The preparation of nano-level precious metal catalysts without cyanide electroplating has problems such as slow deposition speed, unstable coating and low efficiency. At the same time, the carbon monoxide current density generated when electrocatalyzed carbon dioxide reduction in aqueous solution is very low, and the cathode is easily poisoned.
In the organic composite electrolyte, a nano-level precious metal catalyst composite electrode is prepared by constant voltage electrolysis using a noble metal electrode as an anode and a conductive material as a cathode; then the composite electrode is used as a cathode and a constant voltage electrolysis is performed at a tank voltage of 4.5 to 8.5V to generate carbon monoxide and lithium carbonate, and at the same time, chlorine is generated, with a current density exceeding 120mA·cm-2.
The efficient preparation of nano-scale precious metal catalysts and the high efficiency of electrocatalytic reduction of carbon dioxide were achieved, the Faraday efficiency of carbon monoxide was exceeded 82%, and the catalytic performance was maintained for a long time.
Smart Images

Figure BDA0005169100150000021 
Figure BDA0005169100150000022 
Figure BDA0005169100150000031
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing a nanometer-level noble metal catalyst by cyanide-free electroplating and application thereof in electrocatalytic reduction of carbon dioxide, belonging to the technical field of preparation and application of noble metal catalysts. Background Art
[0002] In the field of electrocatalysis, the demand for precious metals has increased significantly due to their excellent conductivity and stability. Electroplating precious metal technology has significantly reduced costs by reducing the amount of materials used, enabling more industries to fully utilize the superior properties of precious metals and expand their applications. Although traditional cyanide electroplating is widely used in the electronics, jewelry and automotive industries, it also faces many challenges, such as environmental pollution, technical complexity, storage and transportation risks, high costs for cyanide wastewater treatment, and strict regulatory requirements. Cyanide-free electroplating of precious metals is increasingly gaining attention as an environmentally friendly alternative. This process uses non-toxic compounds and achieves the deposition of precious metals through electrochemical reactions. In recent years, researchers have improved the deposition quality and efficiency of cyanide-free electroplating by optimizing the process formula. However, cyanide-free electroplating still faces problems such as slow deposition speed, unstable coating and low efficiency. Therefore, the development of new electroplating technologies that are efficient, environmentally friendly, non-toxic, have strong adhesion and are easy to control has become an urgent need in the field of electroplating precious metals.
[0003] Driven by renewable electricity, the electroreduction of carbon dioxide to carbon monoxide and the generation of high-value chemicals is an important way to achieve the recycling of carbon resources. The H-type electrolytic cell is used to electroreduced carbon dioxide in aqueous solution. Due to the low solubility of carbon dioxide in water, the current density of the generated carbon monoxide is very low, which limits its industrial application. To solve this mass transfer limitation, some researchers use gas diffusion electrodes to convert carbon dioxide into carbon monoxide, achieving a current density of more than 100mA / cm 2 However, this method is prone to problems such as electrode poisoning and component oxidation during long-term electrolysis, which limits its large-scale application. In addition, solid oxide electrolysis cell, another commonly used carbon dioxide electroreduction system, can achieve high current density carbon monoxide production at high temperature, but the cathode and anode are easily poisoned and deactivated, so it is still in the laboratory research stage. Summary of the invention
[0004] Aiming at the problems of slow deposition speed, unstable coating and low efficiency in preparing nano-level precious metal catalysts by cyanide-free electroplating, and very low current density of generated carbon monoxide and easy poisoning of cathode in electrocatalytic reduction of carbon dioxide in aqueous solution, the present invention provides a method for preparing nano-level precious metal catalysts by cyanide-free electroplating and application in electrocatalytic reduction of carbon dioxide, namely, in an organic composite electrolyte, a precious metal electrode is used as an anode and a conductive material is used as a cathode, and constant voltage electrolysis is performed to prepare a nano-level precious metal catalyst composite electrode; then, the nano-level precious metal catalyst composite electrode is used as a cathode, a graphite electrode, a glassy carbon electrode or a coated titanium electrode is used as an anode, an organic electrolytic solution is used as a cathode electrolyte, and a saturated lithium chloride aqueous solution is used as an anode electrolyte, and constant voltage electrolysis is performed at a cell voltage of 4.5-8.5V, carbon monoxide is generated at the cathode, lithium carbonate is generated at the same time, and chlorine is generated at the anode, and the current density exceeds 120mA·cm -2 , the Faraday efficiency of carbon monoxide exceeds 82%; after 50 hours of electrolysis, the Faraday efficiency of generating carbon monoxide can still reach 78%; the nano-sized precious metal catalyst has excellent catalytic performance in the long-term catalytic reaction of carbon dioxide electroreduction. The electroplating method of the nano-sized precious metal catalyst provided by the present invention has the advantages of simple process, environmentally friendly electroplating solution, no toxic substances generated, strong coating adhesion, etc.
[0005] A method for preparing a nano-sized noble metal catalyst by cyanide-free electroplating, the specific steps are as follows:
[0006] (1) Using a noble metal electrode as an anode, an organic composite electrolyte as an electroplating solution, and a conductive material as a cathode, inserting the anode and the cathode into the electroplating solution of a single-chamber electrolytic cell at room temperature;
[0007] (2) Constant voltage electrolysis is performed at a cell voltage of 0.5 to 3.0 V to cause the noble metal to undergo oxidation reaction at the anode to generate noble metal ions Me n+ , some noble metal ions Me n+ It forms a complex with the ligand in the organic composite electrolyte to form a noble metal ion. The noble metal ion Me that is not complexed with the ligand n+ The noble metal ions and complexes pass through the organic composite electrolyte, are reduced to nano-sized noble metals at the cathode and deposited on the cathode surface to form a nano-sized noble metal catalyst composite electrode.
[0008] Preferably, the noble metal electrode in step (1) is a single noble metal electrode or a noble metal alloy electrode, the single noble metal electrode is a gold electrode, a platinum electrode or a silver electrode, and the noble metal alloy electrode is a noble metal alloy formed by two or three of gold, platinum and silver.
[0009] Preferably, the organic composite electrolyte in step (1) comprises an organic solvent, a supporting electrolyte and an additive, wherein the organic solvent is one or more of diethyl carbonate, ethylene carbonate, propylene carbonate, ethyl acetate, ethyl butyrate, dimethyl sulfoxide, tetrahydrofuran, cyclohexane, dimethylacetamide, benzene, chloroform and diethyl ether, the supporting electrolyte is a quaternary ammonium salt, and the additive is one or more of imidazole ionic liquids, pyridine ionic liquids, metal porphyrin compounds and metal phthalocyanine compounds.
[0010] Preferably, the quaternary ammonium salt has the chemical structural formula:
[0011]
[0012] R1, R2, R3, R4 are C1-C5 hydrocarbon chains, X - Cl - Br - ,I - 、BF4 - PF6 - 、CH3COO - 、C6H5COO - , C 16 H 33 SO4 - 、SO4 2- 、ClO3 - 、ClO4 - PO4 3- 、CuCl2 - 、AgCl2 - Any one of .
[0013] Preferably, the imidazole ionic liquid has a chemical structural formula:
[0014]
[0015] R1 and R2 are C1-C5 hydrocarbon chains; M and N are hydrogen atoms or functional groups connected to the hydrocarbon chains, and the functional groups are: -NH2 or -OH; X - Cl - Br - 、BF4 - PF6 - 、SO4 2- 、SO3 2- 、HSO4 - 、NO3 - 、ClO3 - PO4 3- 、CH3COO - 、C6H5COO - 、C8H 17 COO- 、CH3SO3 - CF3COO - 、NiCl4 2- 、FeCl4 - 、AlCl4 - 、CuCl2 - 、AgCl2 - 、N(SO3)2 - 、CH3O2 - Any one of .
[0016] Preferably, the structural formula of the pyridine ionic liquid is:
[0017]
[0018] Wherein, R is a C1-C5 hydrocarbon chain, M is a functional group or hydrogen atom connected to the hydrocarbon chain, and the functional group is: -NH2, -CN or -OH; X - Cl - Br - ,I - 、BF4 - PF6 - 、SO4 2- 、SO3 2- 、NO3 - 、ClO4 - 、HSO4 - PO4 3- 、CH3COO - CF3COO - 、CuCl2 - 、AgCl2 - 、NiCl4 2- 、FeCl4 - 、AlCl4 - Any one of .
[0019] Preferably, the metal porphyrin compound has a chemical structural formula:
[0020]
[0021] M1 is any one of iron, cobalt and nickel, and R1, R2, R3 and R4 are hydrogen atoms or C1-C5 hydrocarbon chains, or benzene substituents.
[0022] The metal phthalocyanine compound has the chemical structural formula:
[0023]
[0024] M2 is iron, manganese, copper or nickel.
[0025] Preferably, the content of the supporting electrolyte in the organic composite electrolyte is 0.1-4.0 mol / L, and the content of the additive is 0.01-0.5 mol / L.
[0026] Preferably, the conductive material in step (1) is one or more of a single metal material, an alloy material, a conductive polymer material, a MOF-metal organic framework material, and a conductive carbon-based material.
[0027] More preferably, the elemental metal material is iron, steel, copper, nickel, zinc, aluminum, lead or titanium; the alloy material is bronze, brass, aluminum alloy, steel alloy, nickel alloy, titanium alloy, aluminum bronze, nickel bronze or tungsten alloy; the conductive polymer material is polyaniline, polypyrrole, polyethylenedioxythiophene or polythiophene; the MOF-metal organic framework material is MOF-5, ZIF-8, ZIF-67, UiO-66, MIL-101, MIL-53, IRMOF series, HKUST-1 or PCN-222; the conductive carbon-based material is carbon cloth, carbon felt, conductive sponge, activated carbon, carbon nanotubes, graphite, graphene or carbon fiber.
[0028] Preferably, the ligand in step (2) may be Cl - or Br - ; The ligand is derived from an organic composite electrolyte containing chloride or bromide.
[0029] The noble metal ion of the complex can be [AuCl4] - 、[AuBr4] - , [AgCl2] - , [AgBr2] - , [PtCl4] 2- , [PtBr4] 2- .
[0030] The application of the nano-sized noble metal catalyst in the electrocatalytic reduction of carbon dioxide reaction comprises the following specific steps:
[0031] 1) Using a nano-scale precious metal catalyst composite electrode as a cathode, a graphite electrode, a glassy carbon electrode or a coated titanium electrode as an anode, and a cation exchange membrane as a diaphragm to divide the electrolytic cell into a cathode cell and an anode cell, the cathode cell is filled with a cathode electrolyte, the anode cell is filled with an anode electrolyte, an organic electrolytic solution is used as a cathode electrolyte, and a saturated lithium chloride aqueous solution is used as an anode electrolyte;
[0032] 2) Insert the cathode into the cathode electrolyte of the cathode cell, insert the anode into the anode electrolyte of the anode cell, and perform constant voltage electrolysis at a cell voltage of 4.5 to 8.5 V. Carbon dioxide undergoes an electro-reduction reaction at the cathode to generate carbon monoxide and carbonate ions, and chloride ions undergo an electro-oxidation reaction at the anode to generate chlorine gas. The lithium ions in the anode electrolyte pass through the cation exchange membrane and enter the cathode chamber electrolyte to react with carbonate ions to generate lithium carbonate.
[0033] Preferably, the solvent of the organic electrolytic solution in step 1) is one or more of propylene carbonate, dimethyl sulfoxide, N-methylpyrrolidone, N,N-dimethylformamide, and methanol; the electrolyte is one or more of tetrabutyl salt, imidazole ionic liquid, and pyridine ionic liquid.
[0034] More preferably, the electrolyte tetrabutyl salt is tetrabutylammonium perchlorate, tetrabutylammonium chloride, tetrabutylammonium bromide, tetrabutylammonium iodide, tetrabutylammonium trifluoromethylsulfonate or tetrabutylammonium p-toluenesulfonate; the electrolyte imidazole ionic liquid is 1-ethyl-3-methylimidazolium chloride, 1-ethyl-3-methylimidazolium tetrafluoroborate, 1-ethyl-3-methylimidazolium fluoride, 1-butyl-3-methylimidazolium chloride or 1-methyl-3-cyclohexylimidazolium chloride; the electrolyte pyridine ionic liquid is 1-ethyl-3-methylpyridine chloride, 1-methylpyridine chloride, 1-ethyl-4-methylpyridine tetrafluoroborate, 1-ethyl-4-methylpyridine chloride or 1-ethyl-4-phenylpyridine chloride;
[0035] Preferably, the electrolyte concentration in the organic electrolytic solution in step 1) is 0.1 to 8.0 mol / L.
[0036] The beneficial effects of the present invention are:
[0037] (1) The method of the present invention for cyanide-free electroplating of nano-sized noble metal catalysts significantly reduces production costs by reducing the amount of materials used, thereby making more effective use of the superior properties of noble metals in multiple fields, especially improving product quality in high-end manufacturing, electronic products and catalyst applications; compared with the use of pure noble metals, this process achieves high-performance products with lower investment, thus expanding the application range of noble metals;
[0038] (2) The cyanide-free electroplating process of the present invention is carried out in an organic composite electrolyte, the process is simpler and the cost of raw materials is low. This simplification not only improves the convenience of operation, but also enhances safety, making the production process more stable and controllable; at the same time, it ensures good adhesion and electroplating effect, and improves the reliability and efficiency of the overall process;
[0039] (3) The cyanide-free electroplating of the present invention can eliminate the risk of high toxicity of cyanide used in cyanide electroplating;
[0040] (4) The cyanide-free electroplating technology of the present invention can flexibly prepare high-efficiency catalysts according to different catalytic requirements and is widely used in reactions such as carbon dioxide electroreduction, oxygen evolution and hydrogen evolution;
[0041] (5) The present invention uses a nano-sized noble metal catalyst composite electrode as a cathode, a graphite electrode, a glassy carbon electrode or a coated titanium electrode as an anode, an organic electrolytic solution as a cathode electrolyte, and a saturated lithium chloride aqueous solution as an anode electrolyte. The electrolysis is carried out at a constant voltage of 4.5 to 8.5 V to generate carbon monoxide at the cathode and lithium carbonate at the same time, and chlorine gas is generated at the anode. The current density exceeds 120 mA cm -2 , the Faradaic efficiency of carbon monoxide exceeds 82%; after 50 hours of electrolysis, the Faradaic efficiency of generating carbon monoxide can still reach 78%. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] Figure 1 This is a scanning electron microscope image (magnification 200 times) of example 1 of nano-precious metal gold electroplated onto a foam copper electrode in an organic composite electrolyte without cyanide.
[0043] Figure 2 This is a scanning electron microscope image (magnification 200 times) of example 2 of nanometer noble metal silver electroplated onto a copper sheet electrode in an organic composite electrolyte without cyanide.
[0044] Figure 3 This is a scanning electron microscope image (magnification 120 times) of Example 3 of nano-precious metal silver electroplated on a carbon paper electrode in an organic composite electrolyte without cyanide.
[0045] Figure 4 This is a scanning electron microscope image (magnification 120 times) of example 4 of nanometer noble metal silver electroplated onto a foam copper electrode in an organic composite electrolyte without cyanide.
[0046] Figure 5 This is a scanning electron microscope image (magnification 200 times) of example 5 of nanometer noble metal silver electroplated on a foam nickel electrode in an organic composite electrolyte without cyanide.
[0047] Figure 6 This is a scanning electron microscope image (magnification 1100 times) of Example 6 of nanometer noble metal silver electroplated on a foam copper electrode in an organic composite electrolyte without cyanide.
[0048] Figure 7 This is a scanning electron microscope image (magnification 9000 times) of Example 7 of nanometer noble metal gold electroplated onto a foam copper electrode in an organic composite electrolyte without cyanide.
[0049] Figure 8 This is a scanning electron microscope image (magnification 500 times) of Example 8 of cyanide-free electroplating of nano-precious metal gold onto a foam zinc electrode in an organic composite electrolyte. DETAILED DESCRIPTION
[0050] The present invention is further described in detail below in conjunction with specific implementation modes, but the protection scope of the present invention is not limited to the described contents.
[0051] Example 1: A method for preparing nano-sized noble metal catalysts by cyanide-free electroplating, the specific steps are as follows:
[0052] (1) A noble metal electrode (gold electrode) is used as an anode, an organic composite electrolyte is used as an electroplating solution, and a foam copper electrode is used as a cathode. At room temperature, the anode and the cathode are inserted into the electroplating solution of a single-chamber electrolytic cell; the organic composite electrolyte comprises an organic solvent (propylene carbonate), a supporting electrolyte (tetrabutylammonium chloride) and an additive (iron porphyrin), wherein the concentration of the supporting electrolyte (tetrabutylammonium chloride) in the organic composite electrolyte is 0.1 mol / L, and the concentration of the additive (iron porphyrin) is 0.01 mol / L;
[0053] (2) Constant voltage cyanide-free electrolysis is performed at a cell voltage of 0.5 V to cause the precious metal (gold) to undergo oxidation reaction at the anode to generate precious metal ions (Au 3+ ), some precious metal ions (Au 3+ ) and ligand (Cl - ) complexes to form a noble metal ion [AuCl4]-, but not with the ligand (Cl - ) complexed noble metal ions (Au 3+ ) and the complex noble metal ion [AuCl4]- pass through the organic composite electrolyte, are reduced to nano-sized noble metal (Au) at the cathode (foam copper electrode) and deposited on the surface of the cathode (foam copper electrode) to form a nano-sized noble metal catalyst composite electrode;
[0054] The scanning electron microscope image of the nano-precious metal gold electroplated onto the foam copper electrode in the organic composite electrolyte without cyanide in this embodiment is shown in FIG. Figure 1 ,from Figure 1 It can be seen that Au is uniformly deposited on the surface of the copper foam, showing a granular morphology, with a high and uniform particle distribution density, and no obvious agglomeration phenomenon, indicating that the electroplating process is well controlled; the porous structure of the copper foam is clearly visible, the Au particle deposition does not block the pores, and has good coverage, completely covering the substrate surface, showing high adhesion, and providing a good structural foundation for subsequent electrocatalytic performance applications;
[0055] The application of the nano-sized noble metal catalyst in the electrocatalytic reduction of carbon dioxide reaction comprises the following specific steps:
[0056] 1) A nano-sized noble metal catalyst composite electrode is used as a cathode, a graphite electrode is used as an anode, and a cation exchange membrane (Nafion117) is used as a diaphragm to divide an electrolytic cell into a cathode cell and an anode cell, the cathode cell is filled with a cathode electrolyte, and the anode cell is filled with an anode electrolyte, an organic electrolytic solution is used as a cathode electrolyte, and a saturated lithium chloride aqueous solution is used as an anode electrolyte; the solvent of the organic electrolytic solution is dimethyl sulfoxide, the electrolyte is tetrabutylammonium perchlorate, and the concentration of the electrolyte (tetrabutylammonium perchlorate) in the organic electrolytic solution is 0.1 mol / L;
[0057] 2) inserting the cathode into the cathode electrolyte of the cathode cell, inserting the anode into the anolyte of the anode cell, and electrolyzing at a constant voltage at a cell voltage of 4.5 V, wherein carbon dioxide undergoes an electroreduction reaction at the cathode to generate carbon monoxide and carbonate ions, and chloride ions undergo an electrooxidation reaction at the anode to generate chlorine gas, and lithium ions in the anolyte pass through the cation exchange membrane and enter the electrolyte of the cathode chamber to react with carbonate ions to generate lithium carbonate;
[0058] The current density of this embodiment is 135 mA·cm -2 , the Faraday efficiency of carbon monoxide reaches 82%; after 50 hours of electrolysis, the Faraday efficiency of carbon monoxide production can reach 78%.
[0059] Example 2: A method for preparing nano-sized noble metal catalysts by cyanide-free electroplating, the specific steps are as follows:
[0060] (1) A noble metal electrode (silver electrode) is used as an anode, an organic composite electrolyte is used as an electroplating solution, and a copper sheet electrode is used as a cathode. At room temperature, the anode and the cathode are inserted into the electroplating solution of a single-chamber electrolytic cell; the organic composite electrolyte comprises an organic solvent (diethyl carbonate), a supporting electrolyte (tetrabutylammonium bromide) and an additive (cobalt phthalocyanine); the concentration of the supporting electrolyte (tetrabutylammonium bromide) in the organic composite electrolyte is 0.3 mol / L, and the concentration of the additive (cobalt phthalocyanine) is 0.05 mol / L;
[0061] (2) Constant voltage cyanide-free electrolysis is performed at a cell voltage of 1.0 V to cause the precious metal (silver) to undergo oxidation reaction at the anode to generate precious metal ions (Ag + ), some precious metal ions (Ag + ) and ligand (Br - ) complexes to form a noble metal ion [AgBr2]-, but not with the ligand (Br - ) complexed noble metal ions (Ag + ) and the complex noble metal ion [AgBr2]- pass through the organic composite electrolyte, are reduced to nano-sized noble metal (Ag) at the cathode (copper sheet electrode) and deposited on the surface of the cathode (copper sheet electrode) to form a nano-sized noble metal catalyst composite electrode;
[0062] The scanning electron microscope image of the nano-precious metal gold electroplated onto the foam copper electrode in the organic composite electrolyte without cyanide in this embodiment is shown in FIG. Figure 2 ,from Figure 2 It can be seen that the morphology of Ag deposited on the surface of the copper sheet is more uniform and flat, with no obvious particles or porous structures. The deposition distribution may be relatively continuous due to the smoothness of the substrate. From the surface observation, the electroplated metal Ag layer is in the form of a thin film with low surface roughness, but there are still some tiny protrusions and slight uneven distribution, which may be caused by different local deposition rates during the electroplating process. The overall morphology shows that the electroplating process can achieve relatively uniform coverage on a smooth substrate;
[0063] The application of the nano-sized noble metal catalyst in the electrocatalytic reduction of carbon dioxide reaction comprises the following specific steps:
[0064] 1) A nano-sized noble metal catalyst composite electrode is used as a cathode, a graphite electrode is used as an anode, and a cation exchange membrane (Nafion117) is used as a diaphragm to divide an electrolytic cell into a cathode cell and an anode cell, the cathode cell is filled with a cathode electrolyte, and the anode cell is filled with an anode electrolyte, an organic electrolytic solution is used as a cathode electrolyte, and a saturated lithium chloride aqueous solution is used as an anode electrolyte; the solvent of the organic electrolytic solution is propylene carbonate, the electrolyte is 1-ethyl-3-methylimidazolium tetrafluoroborate, and the concentration of the electrolyte (1-ethyl-3-methylimidazolium tetrafluoroborate) in the organic electrolytic solution is 0.5 mol / L;
[0065] 2) inserting the cathode into the cathode electrolyte of the cathode cell, inserting the anode into the anolyte of the anode cell, and electrolyzing at a constant voltage at a cell voltage of 4.5 V, wherein carbon dioxide undergoes an electroreduction reaction at the cathode to generate carbon monoxide and carbonate ions, and chloride ions undergo an electrooxidation reaction at the anode to generate chlorine gas, and lithium ions in the anolyte pass through the cation exchange membrane and enter the electrolyte of the cathode chamber to react with carbonate ions to generate lithium carbonate;
[0066] The current density in this embodiment is 125 mA·cm -2 , the Faraday efficiency of carbon monoxide reaches 85%; after 50 hours of electrolysis, the Faraday efficiency of generating carbon monoxide can reach 80%.
[0067] Example 3: A method for preparing nano-sized noble metal catalysts by cyanide-free electroplating, the specific steps are as follows:
[0068] (1) A noble metal electrode (silver electrode) is used as an anode, an organic composite electrolyte is used as an electroplating solution, and a carbon paper electrode is used as a cathode. At room temperature, the anode and the cathode are inserted into the electroplating solution of a single-chamber electrolytic cell; the organic composite electrolyte comprises an organic solvent (ethyl acetate), a supporting electrolyte (tetrabutylammonium perchlorate) and an additive (1-ethyl-3-methylimidazolium chloride); the concentration of the supporting electrolyte (tetrabutylammonium perchlorate) in the organic composite electrolyte is 0.3 mol / L, and the concentration of the additive (1-ethyl-3-methylimidazolium chloride) is 0.1 mol / L;
[0069] (2) Constant voltage cyanide-free electrolysis is performed at a cell voltage of 1.5 V to cause the precious metal (silver) to undergo oxidation reaction at the anode to generate precious metal ions (Ag + ), some precious metal ions (Ag + ) and ligand (Cl - ) complexes to form a noble metal ion [AgCl2]-, but not with the ligand (Cl - ) complexed to obtain precious metal ions (Ag + ) and the complex noble metal ion [AgCl2]- pass through the organic composite electrolyte, are reduced to nano-sized noble metal (Ag) at the cathode (carbon paper electrode) and deposited on the surface of the cathode (carbon paper electrode) to form a nano-sized noble metal catalyst composite electrode;
[0070] The scanning electron microscope image of the nano-precious metal gold electroplated onto the foam copper electrode in the organic composite electrolyte without cyanide in this embodiment is shown in FIG. Figure 3 ,from Figure 3 It can be seen that the surface of the mesh structure of carbon paper fibers is covered with a large number of deposited silver particles; the distribution of silver particles is uneven, some areas show high aggregation, forming particle clusters, while other areas are covered thinly; this morphology may be caused by the pores on the surface of carbon paper and the local electric field enhancement effect of fibers; the overall size distribution range of particles is wide, some particles are large and even merged with adjacent particles, while small particles are evenly distributed on the fiber surface; in addition, the three-dimensional porous structure of carbon paper helps to increase the adhesion area of the electroplating layer, thereby increasing the loading amount of the catalyst;
[0071] The application of the nano-sized noble metal catalyst in the electrocatalytic reduction of carbon dioxide reaction comprises the following specific steps:
[0072] 1) A nano-sized noble metal catalyst composite electrode is used as a cathode, a graphite electrode is used as an anode, and a cation exchange membrane (Nafion117) is used as a diaphragm to divide an electrolytic cell into a cathode cell and an anode cell, the cathode cell is filled with a cathode electrolyte, and the anode cell is filled with an anode electrolyte, an organic electrolytic solution is used as a cathode electrolyte, and a saturated lithium chloride aqueous solution is used as an anode electrolyte; the solvent of the organic electrolytic solution is N-methylpyrrolidone, the electrolyte is 1-ethyl-4-methylpyridine tetrafluoroborate, and the concentration of the electrolyte (1-ethyl-4-methylpyridine tetrafluoroborate) in the organic electrolytic solution is 5 mol / L;
[0073] 2) inserting the cathode into the cathode electrolyte of the cathode cell, inserting the anode into the anolyte of the anode cell, and electrolyzing at a constant voltage at a cell voltage of 6.5 V, wherein carbon dioxide undergoes an electroreduction reaction at the cathode to generate carbon monoxide and carbonate ions, and chloride ions undergo an electrooxidation reaction at the anode to generate chlorine gas, and lithium ions in the anolyte pass through the cation exchange membrane and enter the electrolyte of the cathode chamber to react with carbonate ions to generate lithium carbonate;
[0074] The current density of this embodiment is 128 mA·cm -2 , the Faraday efficiency of carbon monoxide reaches 83%; after 50 hours of electrolysis, the Faraday efficiency of carbon monoxide production can reach 79%.
[0075] Example 4: A method for preparing nano-sized noble metal catalysts by cyanide-free electroplating, the specific steps are as follows:
[0076] (1) A noble metal electrode (silver electrode) is used as an anode, an organic composite electrolyte is used as an electroplating solution, and a foam copper electrode is used as a cathode. At room temperature, the anode and the cathode are inserted into the electroplating solution of a single-chamber electrolytic cell; the organic composite electrolyte comprises an organic solvent (tetrahydrofuran), a supporting electrolyte (tetrabutylammonium trifluoromethylsulfonate) and an additive (1-methylpyridinium chloride); the concentration of the supporting electrolyte (tetrabutylammonium trifluoromethylsulfonate) in the organic composite electrolyte is 0.3 mol / L, and the concentration of the additive (1-methylpyridinium chloride) is 0.3 mol / L;
[0077] (2) Constant voltage cyanide-free electrolysis is performed at a cell voltage of 2.0 V to cause the precious metal (silver) to undergo oxidation reaction at the anode to generate precious metal ions (Ag + ), some precious metal ions (Ag + ) and ligand (Cl - ) complexes to form a noble metal ion [AgCl2]-, but not with the ligand (Cl - ) complexed noble metal ions (Ag +) and the complex noble metal ion [AgCl2]- pass through the organic composite electrolyte, are reduced to nano-sized noble metal (Ag) at the cathode (foam copper electrode) and deposited on the surface of the cathode (foam copper electrode) to form a nano-sized noble metal catalyst composite electrode;
[0078] The scanning electron microscope image of the nano-precious metal gold electroplated onto the foam copper electrode in the organic composite electrolyte without cyanide in this embodiment is shown in FIG. Figure 4 ,from Figure 4 It can be seen that through the cyanide-free electroplating process, silver particles are evenly distributed on the porous structure surface of the copper foam, and the deposited layer is granular, with small particle size and uniform distribution, without obvious agglomeration or uneven deposition; the silver particles are mainly attached to the pore wall and surface of the copper foam, and do not block the pores, maintaining the original porous structure of the copper foam; this uniform silver deposition not only increases the silver loading, but also helps to maintain a high specific surface area, providing an excellent substrate for subsequent electrocatalysis and other applications;
[0079] The application of the nano-sized noble metal catalyst in the electrocatalytic reduction of carbon dioxide reaction comprises the following specific steps:
[0080] 1) A nano-sized noble metal catalyst composite electrode is used as a cathode, a graphite electrode is used as an anode, and a cation exchange membrane (Nafion117) is used as a diaphragm to divide an electrolytic cell into a cathode cell and an anode cell, the cathode cell is filled with a cathode electrolyte, and the anode cell is filled with an anode electrolyte, an organic electrolytic solution is used as a cathode electrolyte, and a saturated lithium chloride aqueous solution is used as an anode electrolyte; the solvent of the organic electrolytic solution is methanol, the electrolyte is tetrabutylammonium benzenesulfonate, and the concentration of the electrolyte (tetrabutylammonium benzenesulfonate) in the organic electrolytic solution is 8.0 mol / L;
[0081] 2) inserting the cathode into the cathode electrolyte of the cathode cell, inserting the anode into the anolyte of the anode cell, and electrolyzing at a constant voltage at a cell voltage of 7.5 V, wherein carbon dioxide undergoes an electroreduction reaction at the cathode to generate carbon monoxide and carbonate ions, and chloride ions undergo an electrooxidation reaction at the anode to generate chlorine gas, and lithium ions in the anolyte pass through the cation exchange membrane and enter the electrolyte of the cathode chamber to react with carbonate ions to generate lithium carbonate;
[0082] The current density of this embodiment is 132 mA·cm -2 , the Faraday efficiency of carbon monoxide reaches 87%; after 50 hours of electrolysis, the Faraday efficiency of carbon monoxide production can reach 83%.
[0083] Example 5: A method for preparing nano-sized noble metal catalysts by cyanide-free electroplating, the specific steps are as follows:
[0084] (1) A noble metal electrode (silver electrode) is used as an anode, an organic composite electrolyte is used as an electroplating solution, and a nickel foam electrode is used as a cathode. At room temperature, the anode and the cathode are inserted into the electroplating solution of a single-chamber electrolytic cell; the organic composite electrolyte comprises an organic solvent (ethyl butyrate), a supporting electrolyte (tetrabutylammonium bromide) and an additive (copper porphyrin); the concentration of the supporting electrolyte (tetrabutylammonium bromide) in the organic composite electrolyte is 4.0 mol / L, and the concentration of the additive (copper porphyrin) is 0.5 mol / L;
[0085] (2) Constant voltage cyanide-free electrolysis is performed at a cell voltage of 3.0 V to cause the precious metal (silver) to undergo oxidation reaction at the anode to generate precious metal ions (Ag + ), some precious metal ions (Ag + ) and ligand (Br - ) complexes to form a noble metal ion [AgBr2]-, but not with the ligand (Br - ) complexed noble metal ions (Ag + ) and the complex noble metal ion [AgBr2]- pass through the organic composite electrolyte, are reduced to nano-sized noble metal (Ag) at the cathode (nickel foam electrode) and deposited on the surface of the cathode (nickel foam electrode) to form a nano-sized noble metal catalyst composite electrode;
[0086] The scanning electron microscope image of the nano-precious metal gold electroplated onto the foam nickel electrode in the organic composite electrolyte without cyanide in this embodiment is shown in FIG. Figure 5 ,from Figure 5 It can be seen that silver particles are evenly deposited on the porous surface of nickel foam, forming a layer of fine silver particles. The silver particles are evenly distributed and small in size, and there is no obvious agglomeration on the surface, indicating that the deposition during the electroplating process is relatively uniform. The porous structure of nickel foam is still clearly visible, and the silver particles are deposited on the pore walls and surfaces without blocking the pores, maintaining the high specific surface area of the substrate;
[0087] The application of the nano-sized noble metal catalyst in the electrocatalytic reduction of carbon dioxide reaction comprises the following specific steps:
[0088] 1) A nano-sized noble metal catalyst composite electrode is used as a cathode, a graphite electrode is used as an anode, and a cation exchange membrane (Nafion117) is used as a diaphragm to divide an electrolytic cell into a cathode cell and an anode cell, the cathode cell is filled with a cathode electrolyte, and the anode cell is filled with an anode electrolyte, an organic electrolytic solution is used as a cathode electrolyte, and a saturated lithium chloride aqueous solution is used as an anode electrolyte; the solvent of the organic electrolytic solution is N,N-dimethylformamide, the electrolyte is tetrabutylammonium perchlorate, and the concentration of the electrolyte (tetrabutylammonium perchlorate) in the organic electrolytic solution is 6.5 mol / L;
[0089] 2) inserting the cathode into the cathode electrolyte of the cathode cell, inserting the anode into the anolyte of the anode cell, and electrolyzing at a constant voltage at a cell voltage of 8.5 V, wherein carbon dioxide undergoes an electroreduction reaction at the cathode to generate carbon monoxide and carbonate ions, and chloride ions undergo an electrooxidation reaction at the anode to generate chlorine gas, and lithium ions in the anolyte pass through the cation exchange membrane and enter the electrolyte of the cathode chamber to react with carbonate ions to generate lithium carbonate;
[0090] The current density of this embodiment is 126 mA·cm -2 , the Faraday efficiency of carbon monoxide reaches 82%; after 50 hours of electrolysis, the Faraday efficiency of carbon monoxide production can reach 79%.
[0091] Example 6: A method for preparing nano-sized noble metal catalysts by cyanide-free electroplating, the specific steps are as follows:
[0092] (1) A noble metal electrode (silver electrode) is used as an anode, an organic composite electrolyte is used as an electroplating solution, and a foam copper electrode is used as a cathode. At room temperature, the anode and the cathode are inserted into the electroplating solution of a single-chamber electrolytic cell; the organic composite electrolyte comprises an organic solvent (dimethyl sulfoxide), a supporting electrolyte (tetramethylammonium chloride) and an additive (1-butyl-3-methylimidazolium chloride); the concentration of the supporting electrolyte (tetrabutylammonium trifluoromethylsulfonate) in the organic composite electrolyte is 0.3 mol / L, and the concentration of the additive (1-butyl-3-methylimidazolium chloride) is 0.3 mol / L;
[0093] (2) Constant voltage cyanide-free electrolysis is performed at a cell voltage of 2.5 V to cause the precious metal (silver) to undergo oxidation reaction at the anode to generate precious metal ions (Ag + ), some precious metal ions (Ag + ) and ligand (Cl - ) complexes to form a noble metal ion [AgCl2]-, but not with the ligand (Cl - ) complexed noble metal ions (Ag + ) and the complex noble metal ion [AgCl2]- pass through the organic composite electrolyte, are reduced to nano-sized noble metal (Ag) at the cathode (foam copper electrode) and deposited on the surface of the cathode (foam copper electrode) to form a nano-sized noble metal catalyst composite electrode;
[0094] The scanning electron microscope image of the nano-precious metal gold electroplated onto the foam copper electrode in the organic composite electrolyte without cyanide in this embodiment is shown in FIG. Figure 6 ,from Figure 6 It can be seen that the silver particles are uniformly deposited on the porous structure surface of the copper foam, forming a layer of agglomerated silver particles with uniform distribution of particles, indicating that the deposition conditions in the electroplating process are relatively optimized and can achieve uniform Ag ball layer deposition;
[0095] The application of the nano-sized noble metal catalyst in the electrocatalytic reduction of carbon dioxide reaction comprises the following specific steps:
[0096] 1) A nano-sized noble metal catalyst composite electrode is used as a cathode, a graphite electrode is used as an anode, and a cation exchange membrane (Nafion117) is used as a diaphragm to divide an electrolytic cell into a cathode cell and an anode cell, the cathode cell is filled with a cathode electrolyte, and the anode cell is filled with an anode electrolyte, an organic electrolytic solution is used as a cathode electrolyte, and a saturated lithium chloride aqueous solution is used as an anode electrolyte; the solvent of the organic electrolytic solution is N,N-dimethylformamide, the electrolyte is tetrabutylammonium perchlorate, and the concentration of the electrolyte (tetrabutylammonium perchlorate) in the organic electrolytic solution is 6.0 mol / L;
[0097] 2) inserting the cathode into the cathode electrolyte of the cathode cell, inserting the anode into the anolyte of the anode cell, and electrolyzing at a constant voltage at a cell voltage of 5.5 V, wherein carbon dioxide undergoes an electroreduction reaction at the cathode to generate carbon monoxide and carbonate ions, and chloride ions undergo an electrooxidation reaction at the anode to generate chlorine gas, and lithium ions in the anolyte pass through the cation exchange membrane and enter the electrolyte of the cathode chamber to react with carbonate ions to generate lithium carbonate;
[0098] The current density of this embodiment is 132.5 mA·cm -2 , the Faraday efficiency of carbon monoxide reaches 89.6%; after 50 hours of electrolysis, the Faraday efficiency of generating carbon monoxide can reach 85.5%.
[0099] Example 7: A method for preparing nano-sized noble metal catalysts by cyanide-free electroplating, the specific steps are as follows:
[0100] (1) A noble metal electrode (gold electrode) is used as an anode, an organic composite electrolyte is used as an electroplating solution, and a foam copper electrode is used as a cathode. At room temperature, the anode and the cathode are inserted into the electroplating solution of a single-chamber electrolytic cell; the organic composite electrolyte comprises an organic solvent (propylene carbonate), a supporting electrolyte (tetrabutylammonium bromide) and an additive (nickel porphyrin); the concentration of the supporting electrolyte (tetrabutylammonium chloride) in the organic composite electrolyte is 2.5 mol / L, and the concentration of the additive (nickel porphyrin) is 0.05 mol / L;
[0101] (2) Constant voltage cyanide-free electrolysis was performed at a cell voltage of 3.0 V to cause the precious metal (gold) to undergo oxidation reaction at the anode to generate precious metal ions (Au 3+ ), some precious metal ions (Au 3+ ) and ligand (Br - ) complexes to form a noble metal ion [AgBr4]-, but not with the ligand (Br - ) complexed noble metal ions (Au 3+) and the complex noble metal ion [AgBr4]- pass through the organic composite electrolyte, are reduced to nano-sized noble metal (Au) at the cathode (foam copper electrode) and deposited on the surface of the cathode (foam copper electrode) to form a nano-sized noble metal catalyst composite electrode;
[0102] The scanning electron microscope image of the nano-precious metal gold electroplated onto the foam copper electrode in the organic composite electrolyte without cyanide in this embodiment is shown in FIG. Figure 7 ,from Figure 7 It can be seen that gold (Au) particles are uniformly deposited on the surface of the foam copper, forming a layer of fine and evenly distributed gold particles. The size of a single gold particle is about 200nm, and there is no obvious agglomeration phenomenon, indicating that the gold particles are deposited more evenly during the electroplating process, ensuring the stability and consistency of the coating.
[0103] The application of the nano-sized noble metal catalyst in the electrocatalytic reduction of carbon dioxide reaction comprises the following specific steps:
[0104] 1) A nano-sized noble metal catalyst composite electrode is used as a cathode, a graphite electrode is used as an anode, and a cation exchange membrane (Nafion117) is used as a diaphragm to divide an electrolytic cell into a cathode cell and an anode cell, the cathode cell is filled with a cathode electrolyte, and the anode cell is filled with an anode electrolyte, an organic electrolytic solution is used as a cathode electrolyte, and a saturated lithium chloride aqueous solution is used as an anode electrolyte; the solvent of the organic electrolytic solution is N-methylpyrrolidone, the electrolyte is tetrabutylammonium chloride, and the concentration of the electrolyte (tetrabutylammonium chloride) in the organic electrolytic solution is 7.5 mol / L;
[0105] 2) inserting the cathode into the cathode electrolyte of the cathode cell, inserting the anode into the anolyte of the anode cell, and electrolyzing at a constant voltage at a cell voltage of 7.0 V, wherein carbon dioxide undergoes an electroreduction reaction at the cathode to generate carbon monoxide and carbonate ions, and chloride ions undergo an electrooxidation reaction at the anode to generate chlorine gas, and lithium ions in the anolyte pass through the cation exchange membrane and enter the electrolyte of the cathode chamber to react with carbonate ions to generate lithium carbonate;
[0106] The current density of this embodiment is 126.5 mA·cm -2 , the Faraday efficiency of carbon monoxide reaches 83.5%; after 50 hours of electrolysis, the Faraday efficiency of generating carbon monoxide can reach 85.6%.
[0107] Example 8: A method for preparing nano-sized noble metal catalysts by cyanide-free electroplating, the specific steps are as follows:
[0108] (1) A noble metal electrode (gold electrode) is used as an anode, an organic composite electrolyte is used as an electroplating solution, and a foamed zinc electrode is used as a cathode. At room temperature, the anode and the cathode are inserted into the electroplating solution of a single-chamber electrolytic cell; the organic composite electrolyte comprises an organic solvent (dimethylacetamide), a supporting electrolyte (tetrabutylammonium perchlorate) and an additive (1-ethyl-4-phenylpyridinium chloride); the concentration of the supporting electrolyte (tetrabutylammonium perchlorate) in the organic composite electrolyte is 3.5 mol / L, and the concentration of the additive (1-ethyl-4-phenylpyridinium chloride) is 0.2 mol / L;
[0109] (2) Constant voltage cyanide-free electrolysis is performed at a cell voltage of 2.5 V to cause the precious metal (silver) to undergo oxidation reaction at the anode to generate precious metal ions (Au 3+ ), some precious metal ions (Au 3+ ) and ligand (Cl - ) complexes to form a noble metal ion [AuCl4]-, but not with the ligand (Cl - ) complexed noble metal ions (Au 3+ ) and the complex noble metal ion [AuCl4]- pass through the organic composite electrolyte, are reduced to nano-sized noble metal (Au) at the cathode (foam copper electrode) and deposited on the surface of the cathode (foam zinc electrode) to form a nano-sized noble metal catalyst composite electrode;
[0110] The scanning electron microscope image of the nano-precious metal gold electroplated onto the foam zinc electrode in the organic composite electrolyte without cyanide in this embodiment is shown in FIG. Figure 8 ,from Figure 8 It can be seen that gold (Au) particles are uniformly deposited on the surface of zinc foam, forming a uniformly distributed gold nanoflower layer. The size of a single gold nanoflower is about 1μm, and the gold nanoflower has a regular morphology, indicating that during the electroplating process, gold particles are uniformly deposited in a nanoflower-like structure, successfully forming a stable nanoscale gold covering layer. This deposition morphology not only ensures the high specific surface area of the gold nanoflower, but also provides an ideal electrode surface structure for subsequent catalytic applications, enhancing the efficiency and stability of the electrocatalytic reaction;
[0111] The application of the nano-sized noble metal catalyst in the electrocatalytic reduction of carbon dioxide reaction comprises the following specific steps:
[0112] 1) A nano-sized noble metal catalyst composite electrode is used as a cathode, a graphite electrode is used as an anode, and a cation exchange membrane (Nafion117) is used as a diaphragm to divide an electrolytic cell into a cathode cell and an anode cell, the cathode cell is filled with a cathode electrolyte, and the anode cell is filled with an anode electrolyte, an organic electrolytic solution is used as a cathode electrolyte, and a saturated lithium chloride aqueous solution is used as an anode electrolyte; the solvent of the organic electrolytic solution is propylene carbonate, the electrolyte is tetrabutylammonium benzenesulfonate, and the concentration of the electrolyte (tetrabutylammonium benzenesulfonate) in the organic electrolytic solution is 5.0 mol / L;
[0113] 2) inserting the cathode into the cathode electrolyte of the cathode cell, inserting the anode into the anolyte of the anode cell, and electrolyzing at a constant voltage at a cell voltage of 5.5 V, wherein carbon dioxide undergoes an electroreduction reaction at the cathode to generate carbon monoxide and carbonate ions, and chloride ions undergo an electrooxidation reaction at the anode to generate chlorine gas, and lithium ions in the anolyte pass through the cation exchange membrane and enter the electrolyte of the cathode chamber to react with carbonate ions to generate lithium carbonate;
[0114] The current density of this embodiment is 135.2 mA·cm -2 , the Faraday efficiency of carbon monoxide reaches 85.5%; after 50 hours of electrolysis, the Faraday efficiency of generating carbon monoxide can reach 82.6%.
[0115] The specific implementation modes of the present invention are described in detail above, but the present invention is not limited to the above implementation modes, and various changes can be made within the knowledge scope of ordinary technicians in this field without departing from the purpose of the present invention.
Claims
1. A method for preparing nano-sized noble metal catalysts by cyanide-free electroplating, characterized in that: The specific steps are as follows: (1) Using a noble metal electrode as an anode, an organic composite electrolyte as an electroplating solution, and a conductive material as a cathode, inserting the anode and the cathode into the electroplating solution of a single-chamber electrolytic cell at room temperature; (2) Constant voltage electrolysis is performed at a cell voltage of 0.5 to 3.0 V to cause the noble metal to undergo oxidation reaction at the anode to generate noble metal ions Me n+ , some noble metal ions Me n+ It forms a complex with the ligand in the organic composite electrolyte to form a noble metal ion. The noble metal ion Me that is not complexed with the ligand n+ The noble metal ions and complexes pass through the organic composite electrolyte, are reduced to nano-sized noble metals at the cathode and deposited on the cathode surface to form a nano-sized noble metal catalyst composite electrode.
2. The method for preparing nano-sized noble metal catalysts by cyanide-free electroplating according to claim 1, characterized in that: The noble metal electrode in step (1) is a single noble metal electrode or a noble metal alloy electrode. The single noble metal electrode is a gold electrode, a platinum electrode or a silver electrode. The noble metal alloy electrode is a noble metal alloy formed by two or three of gold, platinum and silver.
3. The method for preparing nano-sized noble metal catalysts by cyanide-free electroplating according to claim 1, characterized in that: The organic composite electrolyte in step (1) comprises an organic solvent, a supporting electrolyte and an additive. The organic composite electrolyte comprises an organic solvent, a supporting electrolyte and an additive. The organic solvent is one or more of diethyl carbonate, ethylene carbonate, propylene carbonate, ethyl acetate, ethyl butyrate, dimethyl sulfoxide, tetrahydrofuran, cyclohexane, dimethylacetamide, benzene, chloroform and diethyl ether. The supporting electrolyte is a quaternary ammonium salt. The additive is one or more of imidazole ionic liquids, pyridine ionic liquids, metal porphyrin compounds and metal phthalocyanine compounds.
4. The method for preparing nano-sized noble metal catalysts by cyanide-free electroplating according to claim 3, characterized in that: The content of the supporting electrolyte in the organic composite electrolyte is 0.1-4.0 mol / L, and the content of the additive is 0.01-0.5 mol / L.
5. The method for preparing nano-scale noble metal catalysts by cyanide-free electroplating according to claim 1, characterized in that: The cathode conductive material in step (1) is one or more of a single metal material, an alloy material, a conductive polymer material, a MOF-metal organic framework material, and a conductive carbon-based material.
6. The method for preparing nano-sized noble metal catalysts by cyanide-free electroplating according to claim 5, characterized in that: The elemental metal material is iron, steel, copper, nickel, zinc, aluminum, lead or titanium; the alloy material is bronze, brass, aluminum alloy, steel alloy, nickel alloy, titanium alloy, aluminum bronze, nickel bronze or tungsten alloy; the conductive polymer material is polyaniline, polypyrrole, polyethylenedioxythiophene or polythiophene; the MOF-metal organic framework material is MOF-5, ZIF-8, ZIF-67, UiO-66, MIL-101, MIL-53, IRMOF series, HKUST-1 or PCN-222; the conductive carbon-based material is carbon cloth, carbon felt, conductive sponge, activated carbon, carbon nanotubes, graphite, graphene or carbon fiber.
7. Use of the nanoscale noble metal catalyst prepared by the method of claim 1 in the electrocatalytic reduction of carbon dioxide.
8. The use according to claim 7, characterized in that: The specific steps are as follows: 1) Using a nano-scale precious metal catalyst composite electrode as a cathode, a graphite electrode, a glassy carbon electrode or a coated titanium electrode as an anode, and a cation exchange membrane as a diaphragm to divide the electrolytic cell into a cathode cell and an anode cell, the cathode cell is filled with a cathode electrolyte, the anode cell is filled with an anode electrolyte, an organic electrolytic solution is used as a cathode electrolyte, and a saturated lithium chloride aqueous solution is used as an anode electrolyte; 2) Insert the cathode into the cathode electrolyte of the cathode cell, insert the anode into the anode electrolyte of the anode cell, and perform constant voltage electrolysis at a cell voltage of 4.5 to 8.5 V. Carbon dioxide undergoes electroreduction reaction at the cathode to generate carbon monoxide and carbonate ions, and chloride ions undergo electrooxidation reaction at the anode to generate chlorine. Lithium ions in the anode electrolyte pass through the cation exchange membrane and enter the cathode chamber electrolyte to react with carbonate ions to generate lithium carbonate.
9. The use according to claim 8, characterized in that: Step 1) The solvent of the organic electrolytic solution is one or more of propylene carbonate, dimethyl sulfoxide, N-methylpyrrolidone, N,N-dimethylformamide, and methanol; the electrolyte is one or more of tetrabutyl salt, imidazole ionic liquid, and pyridine ionic liquid.
10. The use according to claim 8, characterized in that: Step 1) The electrolyte concentration in the organic electrolytic solution is 0.1 to 8.0 mol / L.